Permittivity modulation in Si-based PIN diode by electron irradiation. (1st September 2022) - Wang, Yisong; Gong, Min; Li, Yun; Yang, Zhimei; Rong, Chenshuo; Huang, Mingmin; Ma, Yao; Li, Jianghuan
Abstract: In this paper, we investigate the influence of defects induced by different doses of electron irradiation on the real part of permittivity of Si-based PIN diodes with a deep-level transient spectrum test. For a more precise result, the relationship between the real part of the permittivity of the sample and the irradiation dose, temperature and annealing is studied. The results show that the real part of the permittivity changes significantly with the irradiation dose and temperature. The absolute value of the real part of the permittivity decreases with the decrease in temperature, and the changing trend decreases after annealing. The deep-level transient spectroscopy results illustrate that different states of defects caused by radiation and annealing have changed the free carrier mobility, free carrier density and charge balance in the material, which means they have a significant impact on the electrical characteristics of the samples. The I – V and C – V curves are obtained through experiments to extract the leakage current and carrier concentration. The I – V characteristic and the permittivity are subjected to temperature-variation analysis.